A Robust, Streamlined, Enzyme-based DNA Library Preparation Method Amenable to a Wide Range of DNA Inputs - Hoppers, Amanda (J Biomol Tech, 2019)
Advances in next generation sequencing (NGS) platforms have outpaced those in library preparation. While hundreds to thousands of NGS libraries can be sequenced in a single run of an Illumina instrument, a single library is constructed using a multi-step procedure requiring expensive consumables and specialized equipment. To overcome these limitations and increase the ease and throughput of library construction, we have developed a robust, streamlined library construction method that integrates enzyme-based DNA fragmentation with end repair and dA-tailing. The NEBNext Ultra II FS DNA Library Prep Kit eliminates the need for specialized equipment to fragment DNA and reduces the number of steps in the library construction protocol. This method produces high quality libraries from gDNA isolated from organisms whose genomes vary widely in GC content, as well as amplicons and DNA purified from blood. In addition, the FS kit generates libraries with substantially higher yields than those using mechanically sheared DNA, enabling greatly reduced input requirements. Libraries constructed using the FS kit from inputs as low as 100 pg of human gDNA for amplified libraries and 100 ng for PCR free, show similar coverage uniformity and GC bias compared to libraries constructed with 100 ng of mechanically sheared DNA. The ability to generate high quality libraries from low amounts of starting material and a broad range of inputs will help advance the widespread implementation of NGS in both basic science and the clinic.